Isolated Ruptured Tuberculous Splenic Abscess in a Diabetic Patient - Srivastava, Niraj Kumar; Mohanty, Dabajyoti; Singh, Sunita (Indian Journal of Case Reports, 2017)
Tuberculosis should be considered as a diagnostic possibility in patients presenting with pyrexia of unknown origin and splenomegaly; especially, in areas where the disease is prevalent. Splenic involvement is usually seen as a part of milliary form of tuberculosis. Isolated splenic abscess is an extremely rare form of solid organ tuberculosis and is mostly limited to immune compromised patients. This report describes the occurrence of isolated ruptured tuberculous splenic abscess in a man with poorly controlled diabetes mellitus who was successfully managed by splenectomy along with the anti tuberculous treatment.